Chromosome‐level assembly of southern catfish (silurus meridionalis) provides insights into visual adaptation to nocturnal and benthic lifestyles. (12th May 2021) - Zheng, Shuqing; Shao, Feng; Tao, Wenjing; Liu, Zhilong; Long, Juan; Wang, Xiaoshuang; Zhang, Shuai; Zhao, Qingyuan; Carleton, Karen L.; Kocher, Thomas D.; Jin, Li; Wang, Zhijian; et al.
Abstract: The Southern catfish ( Silurus meridionalis ) is a nocturnal and benthic freshwater fish endemic to the Yangtze River and its tributaries. In this study, we constructed a chromosome‐level draft genome of S . meridionalis using 69.7‐Gb Nanopore long reads and 49.5‐Gb Illumina short reads. The genome assembly was 741.2 Mb in size with a contig N50 of 13.19 Mb. An additional 116.4 Gb of Bionano and 77.4 Gb of Hi‐C data were applied to assemble contigs into scaffolds and further into 29 chromosomes, resulting in a 738.9‐Mb genome with a scaffold N50 of 28.04 Mb. A total of 22, 965 protein‐coding genes were predicted from the genome with 22, 519 (98.06%) genes functionally annotated. Comparative genomic and transcriptomic analyses revealed a rod‐dominated visual system which was responsible for scotopic vision. The absence of cone opsins SWS1 and SWS2 resulted in the lack of ultraviolet and blue violet sensitivity. Mutations at key amino acid sites of RH1.1, RH1.2 and RH2 resulted in spectral tuning good for dim light vision and narrow colour vision. A higher expression level of rod phototransduction genes than that of cone genes and higher rod‐to‐cone ratio led to higher optical sensitivity under dim light conditions. In addition, analysis of the genes involved in eye morphogenesis and development revealed the loss of some conserved noncoding elements, which might be associated with the small eyes in catfish. Together, our study provides important clues for the adaptation of the catfish visual system to the nocturnal and benthic lifestyles. The draft genome of S . meridionalis represents a valuable resource for studies of the molecular mechanisms of ecological adaptation.